Le périple d’Edward Snowden - Timothée Giraud; Marta Severo (Netcom)
Facing the deluge of data available on the Internet, one of the most exciting research directions for the social scientist concerns the identification and analysis of social phenomena through this new data. Among these data, some are particularly suitable for the identification of international media events and the study of their diffusion in space and time. We propose to use RSS feeds of daily newspapers. In this paper, we present an analysis of Edward Snowden’s case that provides an optimal example of international media event. Through the description of this story, the media have drawn different geographies mentioning countries that could offer him asylum but also countries potentially affected by the American monitoring policy. We will carry out an analysis of the event by providing a quali-quantitative method based on the analysis of RSS feeds that is expected to solve the dichotomy data quantity-reliability.